Interleukin-27 Inhibits Trophoblast Cell Invasion and Migration by Affecting the Epithelial–Mesenchymal Transition in Preeclampsia. (July 2019) - Ge, Huisheng; Yin, Nanlin; Han, Ting-Li; Huang, Dongni; Chen, Xuehai; Xu, Ping; He, Chengjin; Tong, Chao; Qi, Hongbo
Preeclampsia (PE) is a pregnancy-specific disorder representing a major cause of maternal and perinatal morbidity and mortality. Invasive and migratory phenotypes are acquired by trophoblasts through the process of epithelial–mesenchymal transition (EMT). Studies have shown that trophoblast EMT events are dysregulated in PE and play an important role in its development. Dysregulation of interleukin (IL)-27 and IL-27R (T-cell cytokine receptor (TCCR)/WSX -1) is relevant to PE. In this study, our results demonstrated that IL-27 did not significantly affect the proliferation and apoptosis of HTR -8/SVneo trophoblast cells, while it did significantly inhibit trophoblast invasion and migration. The expression of EMT-related proteins in HTR-8/SVneo cells and extravillous explants was detected after treatment with IL-27. Expression of epithelial markers was increased, and mesenchymal marker expression was reduced. Furthermore, we found that IL-27 could induce significant phosphorylation of Signal Transducer and Activator of Transcription 1 (STAT1) and Signal Transducer and Activator of Transcription 3 (STAT3) in a time-dependent manner in HTR-8/SVneo cells. Selective inhibitors of STAT1 (STAT1 siRNA) and STAT3 (STAT3 siRNA) were used to determine whether both STAT1 and STAT3 are required for IL-27-mediated inhibition of EMT. STAT1 inhibition in IL-27-treated cells attenuated the IL-27 effect, while the inhibition of STAT3 activation had no effect on the development of the epithelial phenotype. These results demonstrate that IL-27 may inhibit trophoblast cell migration and invasion by affecting the EMT process through an STAT1-dominant pathway in PE.